Affect, power, and institutions - Churcher, Millicent; Calkins, Sandra 1982-; Böttger, Jandra; Slaby, Jan 1976- (Routledge, Taylor & Francis Group, 2023)
"This book develops a novel understanding of institutional affect. It explores how institutions produce, frame, and condition affective dynamics and emotional repertoires - in ways that engender conformance or resistance to institutional requirements. The body of research on affect and emotion in social life has largely overlooked an important dimension: institutions. The contributions to this volume advance a comprehensive transdisciplinary approach to the affective life of institutions - theoretical, conceptual, empirical, and critical. In so doing, this book foregrounds oppressive, exploitative, structurally violent or highly biased aspects of institutional arrangements, giving voice to those who struggle with the toxic institutional environments. This book will be important for scholars and students of interdisciplinary affect and emotion studies from a wide range of disciplines, including social sciences, cultural studies, social and cultural anthropology, organizational and institution studies, media studies, social philosophy, aesthetics, and critical theory"--
Keywords: Affekt; Organisationssoziologie; Einrichtung; Machtstruktur; Sozialverhalten; Associations, institutions, etc / Social aspects; Power (Social sciences); Affect (Psychology); Aufsatzsammlung